The management of a trust department - Kennedy, Walter; Searle, Philip F. (Boston : Bankers Pub. Co., 1967)
This book is concerned with the planning, directing, and executing of the varied functions of a trust department, rather than the substantive material of what a trust department does. It is intended for the Executive who directs the trust department, or one who aspires to become such an executive.
usc 16/05/2017
Loans
Keywords: Trust companies